دور أنظمة الجودة الشاملة في رفع الأداء الوظيفي (معايير مع نظام الجودة ISOأنموذجاً) - الأســود, محمود علي أحمد (Al-Qurtas, 2025)
دور أنظمة الجودة الشاملة في رفع الأداء الوظيفي (معايير مع نظام الجودة ISOأنموذجاً)